2020
DOI: 10.1177/1077546320943794
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimal positive position feedback parameters by using nonsmooth H∞ synthesis

Abstract: This article presents a method for determining optimal parameters of positive position feedback controllers used for suppressing vibration of flexible structures. The method is based on solving the H∞ synthesis problem with additional constraints on the controller structure. The method allows for independent control of damping added to each mode. Moreover, optimal parameters for both simple input simple output and multiple input multiple output control formulations can be obtained. The effectiveness of the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The results are presented in graphical forms as steady-state vibration amplitudes (a 1 & a 2 ) against the detuning parameter σ 1 or the excitation amplitude f . In addition, the stability of the obtained solution is investigated according to the condition given by Equation (26). In all obtained response curves, the solid line refers to the stable solution, while the dotted line represents the unstable one.…”
Section: Response Curves and Numerical Validationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are presented in graphical forms as steady-state vibration amplitudes (a 1 & a 2 ) against the detuning parameter σ 1 or the excitation amplitude f . In addition, the stability of the obtained solution is investigated according to the condition given by Equation (26). In all obtained response curves, the solid line refers to the stable solution, while the dotted line represents the unstable one.…”
Section: Response Curves and Numerical Validationsmentioning
confidence: 99%
“…The authors showed that the fractional-order controller is more efficient in suppressing both the periodic and random vibration responses. Also, the optimal design of the positive position feedback controller parameters is introduced using the H 2 and H ∞ optimization techniques [25,26].…”
Section: Introductionmentioning
confidence: 99%